Development of Putri Water Tourism as a Tourist Attraction in Waeyoho, West Seram District, West Seram Regency - Wati, Rahma; Salakory, Melianus; Leuwol, Ferdinand Salomo (Jurnal Pendidikan Geografi Unpatti, 2024)
The definition describes the concept of tourism as an activity that can be identified as "tourism." Tourism includes a series of travel activities carried out for recreational or visiting purposes without the purpose of work or income in the place visited. Tourism involves traveling from one's place of origin to another destination to enjoy new experiences and get to know various places and cultures. Development of Air Putri Tourism as a Tourist Attraction in Waeyoho, West Seram District, West Seram Regency. The analytical descriptive research design with the SWOT method in the cross-section type aims to identify the relationship between variables and analyze a research object's strengths, weaknesses, opportunities, and threats. By focusing on description and data collection, this study does not make general conclusions but rather an in-depth understanding of the conditions observed. In the Development of Air Putri Tourism as a Tourist Attraction in Waiyoho, West Seram District, West Seram Regency. Data can be collected through observation, interviews, questionnaires (questionnaires), and documentation. The population to be used in this study is the Waiyoho Hamlet community, and the sample in this study amounted to 25 people. The results of this study indicate the identification of tourism potential, namely physical conditions, accessibility, and supporting facilities for the community of Kawa village, Waeyoho hamlet, West Seram District, West Seram Regency, Maluku Province.